Juridical Studies On Notary Deed Which Can Be Canceled And Void By The Law And Responsibilities Of Notary According To Law - Arif Bahtiar Jefry; Lathifah Hanim (Jurnal Akta, 2019)
Notary deed can be canceled and void by law because of an error when a deed is contrary to the Act either intentionally or unintentionally by the parties who made it. Deed can be canceled, remain valid and binding as long as there has been no judicial decisions have permanent legal force canceling the deed. Unlike the deed can be canceled due to the manufacturing process does not satisfy the subjective element as set forth in Article 1320 paragraph (1) and (2) of the Civil Code. Deed null and void occurs due to the mechanism of making abuse substance UUJN Regarding the authority of notary in making authentic act and Article 1320 paragraph (3) and (4) of the Civil Code which is the objective conditions in performing an agreement, which is about a certain thing and the cause or causes of the allowed. In UUJN that as a notary in running his offense is proven, the notary must responsibility by way of sanction or sanctions, in the form of civil sanctions, administrative sanctions, criminal sanctions, the code of conduct or a combination of office notary witnesses. In Article 84 UUJN which reads: Actions violations committed by the notary of the provisions referred to in Article 16 paragraph (1) letter i, Article 16 paragraph (1) letter k, Article 41, Article 44, Article 48, Article 49, Article 50 Article 51 or Article 52 that resulted in a deed only has the strength of evidence as the deed under the hand or a certificate becomes null and void may be the reason for the injured party to demand reimbursement of losses, damages, and interest to the notary.Keywords: Notary Deed, Canceled, Cancel By The Law, Responsibility, Notary.